Energy Structure Theory and Energy Hinded Equation (International Journal of Engineering and Computer Science, 2014)
Essence of energy is the action. The essence of structure is the interaction. There are structures in energy. Interactions between energy and material(or energy) are very complex. To the energy absorbing material has certain limitations. A certain energy E interact M mass of the material to make the material move (energy E converted to material kinetic energy). Because the material limit of energy absorption (this energy E is not completely converted to kinetic energy, part of the energy E will be converted to mass), the part of the energy E can not be absorbed to kinetic energy which is called energy hindered,the symbol is Eh. C is the speed of light in vacuum. ΔM is the quality changed of the material in the interaction of energy.